ERG Protein Expression Is of Limited Prognostic Value in Men with Localized Prostate Cancer. (18th August 2013) - Teng, Liang Hong; Wang, Cheng; Dolph, Michael; Donnelly, Bryan; Bismar, Tarek A.
Abstract : Background . The prognostic significance of ERG expression in prostate cancer (PCA) has generated mixed results. We sought to investigate the prognostic significance of ERG expression in a localized cohort of men with PCA. Material and Methods . We investigated ERG protein expression in a cohort of 198 men with localized PCA. ERG expression was correlated with patients' clinical outcome and several pathological parameters, including Gleason score (GS), pathological stage, surgical margin, and extra-capsular extension. Results . ERG expression was detected in 86/198 (43.4%) patients exclusively in neoplastic epithelium. Overall, ERG mean expression intensity was 1.01 ± 1.27 versus 0.37 ± 0.83 in acinar PCA compared to foamy type PCA (P < 0.001 ). In HGPIN, ERG intensity levels were comparable to those in foamy type PCA (0.13 ± 0.56 ) but significantly lower than those in acinar PCA (P < 0.001 ). ERG expression was significantly associated with extra-prostatic extension and higher pathological stage and showed a trend toward seminal vesicle invasion. Herein, ERG expression was documented in 50/131 (38.1%) patients with pT2 versus 30/55 (54.5%) patients with pT3 (P = 0.04 ). ERG association with higher pathological stage was more pronounced in patients with G S > 7 . Grouping patients into those with G S ≤ 7 versus > 7, there was no significant association between ERG expression and GS. Similarly, no association was present in relation to either surgical margins or postsurgical serum PSA levels. Conclusion . We report significant association between ERG protein levels and extra-prostatic extension and higher pathological stage. ERG expression is not associated with adverse clinical outcome and is of limited prognostic value in localized PCA.